Effects of calf compression sleeves on physiological and biomechanical adaptations to trail running - Kerhervé, H.; Samozino, P.; Descombe, F.; Pinay, M.; Millet, G. Y.; Pasqualini, M.; Rupp, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Calf compression sleeves (CS) are increasingly used in off-road exercises, however, no analyses have been conducted so far on the impact of wearing CS on simultaneous physiological and biomechanical adaptations during prolonged (>2 h) outdoor trail running. The aim of this study was therefore to analyse whether CS may modify muscle oxygenation, running biomechanics and performance during a prolonged trail running. Methods: Fourteen healthy trained males (21.7±3.0 yr, 180±5 cm, 72±7 kg) took part in a randomised, cross-over study consisting in two identical 25-km trail running sessions (positive elevation change of 1020 m), >3 weeks apart (same weather conditions). One trial was performed with degressive CS (UP®, Thuasne©, 23±2 mmHg) and the other with control sleeves (CON, <4 mmHg). Oxygenation of the medial gastrocnemius muscle (Mox) was monitored continuously by portable near-infrared spectroscopy (Portalite, Netherland). Biomechanical parameters as ground-contact (Tc) and aerial (Ta) times, duty factor (DF=Tc/[Tc+Ta]), leg stiffness (Kleg) and peak force applied to the ground (Fmax) were determined at 12 km.h-1 using an 8-m long optical system (Optojump, Italy) at the beginning, during, and at the end of both sessions. Exercise-induced Achilles tendon pain (PAT) and delayed onset calf-muscles soreness (DOMS) were assessed using visual analogue scales. Results: Mox increased significantly in CS compared to CON at baseline and immediately after exercise (P<0.05), without any difference in deoxygenation kinetics during the run, irrespective of the slopes (e.g. downhill or uphill sections), and without any significant change in run times (~0.9%). Tc and DF were significantly lower in CS vs. CON and Fmax and Kleg were higher in CS at the beginning and throughout the run. CS and CON induced significant DOMS (> 6 on a 10-cm scale) with no difference between conditions, but PAT after the trial was significantly lesser in CS than CON (P<0.05). Discussion: Calf compression did not modify the `metabolic` state of the muscle during prolonged trail running and exercise-induced DOMS, but minimized Achilles tendon pain at the same level of performance. For the first time, we provided evidence that running mechanics at the beginning and throughout the run are strongly affected by CS. Future research should explore the relationship between such optimisation of the fatigue-induced stride parameters, the reduced pain over the Achilles tendon and performance over longer and/or repeated (chronic) trail running events. ABSTRACT FROM AUTHOR